Asthma in the elderly and late‐onset adult asthma. Issue 2 (7th September 2017) - Dunn, R. M.; Busse, P. J.; Wechsler, M. E.
Abstract: Elderly asthmatics are at a higher risk for morbidity and mortality from their asthma than younger patients. There are important age‐related physiologic and immunologic changes that complicate the presentation, diagnosis, and management of asthma in the aged population. Evidence suggests that elderly asthmatics are more likely to be underdiagnosed and undertreated. Additionally, elderly patients with asthma have highest rates of morbidity and mortality from their disease than younger patients. The underlying airway inflammation of asthma in this age group likely differs from younger patients and is felt to be non‐type 2 mediated. While elderly patients are underrepresented in clinical trials, subgroup analysis of large clinical trials suggests they may be less likely to respond to traditional asthma therapies (ie, corticosteroids). As the armamentarium of pharmacologic asthma therapies expands, it will be critical to include elderly asthmatics in large clinical trials so that therapy may be better tailored to this at‐risk and growing population.